Clonal hematopoiesis and associated diseases: A review of recent findings. Issue 10 (12th August 2021) - Asada, Shuhei; Kitamura, Toshio
Abstract: Recent genome‐wide studies have revealed that aging or chronic inflammation can cause clonal expansion of cells in normal tissues. Clonal hematopoiesis has been the most intensively studied form of clonal expansion in the last decade. Clonal hematopoiesis of indeterminate potential (CHIP) is an age‐related phenomenon observed in elderly individuals with no history of hematological malignancy. The most frequently mutated genes in CHIP are DNMT3A, TET2, and ASXL1, which are associated with initiation of leukemia. Importantly, CHIP has been the focus of a number of studies because it is an independent risk factor for myeloid malignancy, cardiovascular disease (CVD), and all‐cause mortality. Animal models recapitulating human CHIP revealed that CHIP‐associated mutations alter the number and function of hematopoietic stem and progenitor cells (HSPCs) and promote leukemic transformation. Moreover, chronic inflammation caused by infection or aging confers a fitness advantage to the CHIP‐associated mutant HSPCs. Myeloid cells, such as macrophages with a CHIP‐associated mutation, accelerate chronic inflammation and are associated with increased levels of inflammatory cytokines. This positive feedback loop between CHIP and chronic inflammation promotes development of atherosclerosis and chronic heart failure and thereby increases the risk for CVD. Notably, HSPCs with a CHIP‐associated mutation may alter not only innate but also acquired immune cells. This suggests that CHIP is involved in the development of solid cancers or immune disorders, such as aplastic anemia. In this review, we provide an overview of recent findings on CHIP. We also discuss potential interventions for treating CHIP and preventing myeloid transformation and CVD progression. Abstract : In recent years, clonal hematopoiesis has attracted attention from the scientific community because it is an independent risk factor for myeloid malignancy, cardiovascular diseases, and all‐cause mortality. In this review, we summarize the recent significant findings in regard to clonal hematopoiesis and its associated diseases.